IMPLEMENTATION OF THE SCHOOL SOLAR PANEL SYSTEM TO SUPPORT THE AVAILABILITY OF ELECTRICITY SUPPLY AT SDN 4 MESUJI TIMUR - Sampurna Dadi Riskiono; Lulud Oktaviani; Fatimah Mulya Sari (IJISCS (International Journal of Information System and Computer Science), 2021)
Equitable development is always encouraged by both the central and regional governments. However, in practice it is not easy and goes through a fairly long process. Likewise, the efforts of the government, especially the province of Lampung, are trying to carry out development through equal distribution of electrical energy to areas where the National Cross Border Center (PLBN) is located, such as Mesuji Regency, although it is still unstable and uneven throughout the village. The condition of the lack of electricity supply causes blackouts to occur frequently and in a relatively long period of time. This greatly affects community activities and is no exception in terms of education or at school, especially in the use of technology-based learning media and school administrative matters, such as filling out report cards and so on. Nowadays, filling out report cards must be done through technology-based applications that require electronic equipment such as laptops to use them. The design of the School Solar Panel System (SSPS) is intended in an effort to increase the availability of electricity in supporting teacher professionalism in carrying out learning activities. So that with the design of the School Solar Panel System which will be implemented later, the electricity supply remains available even though there is a power outage.